Hidrogeno como sustituto de los combustibles fósiles en Colombia para el sector automotriz. (2022)
This paper presents a detailed analysis of hydrogen as an energy source and aims to discover if this element is the optimal replacement for fossil fuels present in Colombia. As a first instance, the main causes that lead to the realization of this document are examined through the analysis of fossil fuels, followed by the study and investigation of hydrogen as a vehicular fuel and the background prior to this monograph and thus finally make a comparison between these In order to answer the question, is hydrogen the ideal substitute for fossil fuels in Colombia?